Investigation of Rainwater Infiltration Effect on Cracked Soil Using Seepage Analysis - Putu Tantri K. Sari; Himatul Farichah; Yudhi Lastiasih; Indrasurya B. Mochtar (Civil Engineering Journal, 2026)
This research is focused on examining the influence of crack position on slope stability, pore water pressure dynamics, and groundwater level rise induced by prolonged rainfall using seepage analysis. The adoption of a novel integrated method that coupled finite element (SEEP/W) and limit equilibrium (SLOPE/W) analyses led to the introduction of a systematic methodology for evaluating the effectiveness of horizontal drains specifically designed to suit pre-existing crack locations. The results showed that surface cracks in unsaturated soil triggered pore water pressure build-up and groundwater rise, forming localized saturated zones at crack tips after 40 days of continuous rainfall (6 hours/day). Horizontal drains significantly improved stability when positioned near cracks, increasing safety factors by approximately 13% and 6% for slope-surface and mid-slope cracks, respectively. However, it proved ineffective for drains located away from the slope edge. The main novelty centered on quantifying the location-dependent efficacy of drains, establishing a critical zone of influence for optimal drain placement. In addition, the conventional one-size-fits-all method adopted for drain installation was disputed. Field validation using Electrical Resistivity Tomography (ERT) showed that deeper rainwater infiltration realized through cracks during wet seasons supported numerical predictions. The results obtained were in line with the critical role of crack location in drain design. These also provided actionable, location-specific insights for landslide reduction on cracked slopes.